Produção e avaliação de briquetes de resíduos lignocelulósicos - Paula, Luana Elis de Ramos (2010)
Brazil is one of the largest wood and agricultural product producers in the world. Nevertheless, concerning the elevated production, a great amount of residues is generated. These can cause serious environmental problems when overlooked and left indiscriminately in nature. One alternative to minimize the impacts caused by residues is their use for energy production as briquettes. The objectives of this work were: investigating different residues of plant and agroindustry biomass, characterizing them as potentials for energy production, and producing and evaluating briquettes made form these residues. For the fulfillment of this study were utilized wood processing residues (sawdust and shavings); coffee bean parchment and coffee plant stem; bean stem and pod; soybean stem and pod; rice husk, corn leaf, stem, straw and cob and straw and sugar cane bagasse. The assays occurred in the Forest Biomass Energy Laboratory of the Federal University of Lavras. For characterization of the residues were performed the following analyses: immediate chemical analysis, heating value and elementary analysis. Briquetting was performed in a briquetter of the Lippel® brand at pressure of 150 Bar (153 kgf/cm²). It was determined the best briquetting for wood sawing and the best temperature for rice and coffee parchment. For evaluation of the briquetter quality, the apparent relative density, compression resistance and Combustion Index were determined. In general, all the residues showed potential to be utilized in energy production. Rice husk presented the highest lignin content, an interesting feature for energy production; nevertheless, its high ash content brought about a reduction in heating value and fixed carbon. The other kinds of residues showed similar characteristics and best performance of the energy viewpoint. Both briquetting time and temperature interfered in the mechanical resistance of the briquettes. The best pressing time was of eight minutes for sawing and the temperature of best performance was of 125 °C for rice husk and coffee parchment. The briquettes produced from rice husk presented high density and mechanical resistance. The highest combustion index was found for the briquettes of bean pod.